Exclusive Breastfeeding Associated with the Reduction of Acute Respiratory Tract Infections in Toddlers with High-Risk Factors - Abu Bakar; Elfira Fitria Rohma; Iqlima Dwi Kurnia; Siti Nur Qomariah (Universitas Airlangga, 2018)
Introduction: Acute respiratory tract infections (ARI) is a disease that is the primary cause of death, especially in children. Toddlers can be prevented from developing ARI with increased immunity. Giving breast milk can increase children's immunity, but there are still children who experience ARI. This study aimed to explain the differences in Acute Respiratory Tract Infections (ARI) events in toddlers who are exclusively and non-exclusively breastfed.Methods: The research design used was descriptive-comparative with a retrospective design. The population in this study were all children one to three years of age. A sample of 158 toddlers was recruited by a purposive sampling technique. Data retrieval was done with the criteria that the child had visited a public health centre (puskesmas) or integrated health care service post (posyandu), and does not suffer from a disease such as asthma or have any allergies. The variables were measured using a questionnaire and observation sheet. Data analysis was done by a chi-square test and binary logistic regression.Results: The results showed that there were differences in ARI incidence in toddlers (one to three years) who were exclusively and non-exclusively breastfed with a value of p = 0.003. The air pollution factor proved to be significant, dominantly affecting the incidence of ARI.Conclusion: Differences in ARI incidence in toddlers who are exclusively and non-exclusively breastfed is possible due to air pollution factors. Key implications for nursing practice from this research are improving services, and prevent the occurrence of ARI.